Enhanced Removal of Arsenic from Aqueous Medium by Modified Silica Nanospheres: Kinetic and Thermodynamic Studies - Hassan, Asaad F; Hrdina, Radim (Springer, 2022)
In this study, silica nanospheres (S) and trizma base-modified silica nanospheres (ST2, ST4, ST6, and ST8) were synthesized for the removal of arsenic from aqueous medium with high efficiency. Characterization of the prepared solid adsorbents was performed with different techniques such as thermogravimetric analysis, scanning electron microscopy, X-ray diffraction patterns, transmission electron microscopy, selected area electron diffraction, fast Fourier transform, nitrogen adsorption, point of zero charge (pH(PZC)), and Fourier transform infrared. Adsorption of As+5 was investigated under different application conditions such as adsorbent dosage, pH, shaking time, temperature, and initial As+5 concentration. Maximum adsorption capacity reached 64.5 mg/g at pH 6, 0.9 g/L as adsorbent dosage, after 60 min of shaking time, and at 25 degrees C as the optimum adsorption conditions. Adsorption data of As+5 by the prepared nanoadsorbents are best fitted with Langmuir, Temkin, and Dubinin-Radushkevich models. Kinetic studies revealed that the adsorption followed pseudo-second-order and Elovich kinetic models. Thermodynamic studies prove that the adsorption process is endothermic, spontaneous, and chemisorption in nature. The most effective desorption was achieved by nitric acid with 99% desorption efficiency. The prepared silica nanospheres solid adsorbents showed a good reusability with 91% adsorption efficiency after four cycles of adsorption and desorption.
Zlepšené odstraňování arsenu z vodného prostředí pomocí modifikovaných křemičitých nanokuliček: Kinetická a termodynamická studie
Keywords: nanospheres; arsenic; adsorption; desorption; kinetic studies; nanokuličky; arsen; adsorpce; desorpce; kinetická studie